TINJAUAN PENERAPAN EFEKTIVITAS PENGGUNAAN FASILITAS E-FILLING PADA WAJIB PAJAK (Studi Pada Kantor Pelayanan Pajak Pratama Kendari) - Awaluddin, Ishak; Aswati, Wa Ode; Sudarmant, Eko (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
The purpose of this research in knowing Overview Implementation Effectiveness the use of e-filing facility on the taxpayer at the KPP Pratama Kendari. The method of data analysis used in this research is descriptive analysis method.The results of the review in this study indicate that the application of the facility of e-filing in the category very effective for an individual taxpayer, this is because it has been mandatory for civil servants, Police and TNI to switch from reporting manually to reporting e-filing for the use of this e -filing help Annual Tax reporting process is fast, accurate and bureaucratic reporting systems in e-filing tax returns easier when compared with the bureaucratic system manually. means to apply e-filing facilities contribute positively to the individual taxpayer, but not meant for improving the users e-filing is due to a lack of socialization and quality of service.TINJAUAN PENERAPAN EFEKTIVITAS PENGGUNAAN FASILITAS E-FILLING PADA WAJIB PAJAK(Studi Pada Kantor Pelayanan Pajak Pratama Kendari)